ROLE OF LIVER AND BILIARY TRACT DISEASES IN THE DEVELOPMENT OF ABNORMAL UTERINE BLEEDING DUE TO ENDOMETRIAL POLYP - Irnazarova, D.H.; Sadikova, D.R.; Khujaeva, D.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Endometrial polyps (EPs) are a common gynecological condition occurring across all age groups of women. In 2024–2025, 45 women who visited the Multidisciplinary Clinic of the Tashkent Medical Academy were examined and divided into three groups: those with biliary pathology, without biliary pathology, and a control group. The study was conducted using a prospective approach. All participants underwent clinical-anamnestic evaluation, instrumental diagnostics, diagnostic treatment procedures, morphological assessment, and statistical analysis. According to the results of our study, it was found that in women with abnormal uterine bleeding of polyp origin (AUB-P) and coexisting biliary pathology, clinical symptoms of the disease were 1.7–2 times more pronounced compared to women without biliary pathology.